The Macroeconomic Effects of Macroprudential Policy Evidence from a Narrative Approach - Rojas, Diego (The World Bank, 2022)
This paper analyzes the macroeconomic effects of macroprudential policy-in the form of legal reserve requirements-in three Latin American countries (Argentina, Brazil, and Uruguay). To correctly identify innovations in changes in legal reserve requirements, a narrative approach-based on contemporaneous reports from the IMF and central banks in the spirit of Romer and Romer (2010)-is developed in which each change is classified into endogenous or exogenous to the business cycle. This distinction is critical in understanding the macroeconomic effects of reserve requirements. In particular, while output falls in response to exogenous increases in legal reserve requirements, it is not affected when using all changes and relying on traditional time-identifying strategies. This bias reflects the practical relevance of the misidentification of endogenous countercyclical changes in reserve requirements. The empirical frontier is also pushed along two important dimensions. First, in measuring legal reserve requirements, both the different types of legal reserve requirements in terms of maturity and currency of denomination as well as the structure of deposits are taken in account. Second, since in practice reserve requirement policy is tightly linked to monetary policy, the study jointly analyze the macroeconomic effects of changes in central bank interest rates. To properly identify exogenous central bank interest rate shocks, the Romer and Romer (2004) strategy is used
Keywords: Business Cycle; Business Cycles and Stabilization Policies; Economic Policy, Institutions and Governance; Endogeneity; Fiscal and Monetary Policy; Identification; Macroeconomic Effects; Macroprudential Policy; Monetary Policy; Narrative Approach; Reserve Requirements; Stability; Systemic Risk; Macroeconomics and Economic Growth